The Education as a target of Special war - Alispahić, Bakir (Technium Social Sciences Journal, 2021)
War is no longer a conflict between two armies in the battlefield, or a guerrilla fighting in the jungles – war has become much closer, both physically and metaphysically. The 21st century wars are conducted for hearts and minds, and full control of population. Special war, as a war of the fifth generation, incorporates all parts of social life in order to inflict a significant damage upon the target state. The battlefield is no longer hundreds of thousands kilometres away, it is in our immediate proximity – on the social media networks, the places we visit, the books we read or the schools we go to. Subversive measures of indoctrination and propaganda that have penetrated all pores of the society, are currently directed towards education system as an important element for successful and adequate functioning of the state and its society. This paper discusses education as a target of Special war. The author also analyses the ways in which the education can be misused for the realization of some 'higher goals'.